Equity in Health Financing: Review of Health Care financing in Four organizations for economic cooperation development (OECD) countries, Canada, The republic of Korea, Mexico and the United Kingdom - Kinyua, Caroline Gacheri (Health Economics Unit, 2014)
Includes bibliographical references.